Analysis on CO2 Emissions Transferred from Developed Economies to China through Trade. (March 2016) - Zhang, Wencheng; Peng, Shuijun
Abstract: Based on a global input–output model, this paper investigates the CO2 emission transfer between China and developed economies through trade. The results show that approximately 15–23 percent of China's production‐based emissions during 1995–2009 were induced by the production of goods and services satisfying final demand in developed economies. Decomposition of emission transfers shows that trade of intermediate products played a significant role in emission transfer from developed economies to China. Most developed economies have consumption‐based emission responsibilities that are higher than their production‐based responsibilities, whereas China's consumption‐based responsibility is significantly lower than its production‐based responsibility. We argue that a fair and efficient carbon accounting approach should take CO emission transfers from developed economies to developing economies into consideration. It is important that China and its developed trade partners cooperate in reducing emission transfers.